Gambaran Stres dan Mekanisme Koping Petani Di Kecamatan Kalisat-Jember - Ananda Patuh Padaallah; Emi Wuri Wuryaningsih; Alfid Tri Afandi (UPT Percetakan dan Penerbitan Universitas Jember, 2022)
Farmers have a high risk to suffer psychological health pressure. The factors that cause farmers to have psychological pressure are limited land, the decrease in soil fertility, soil degradation, and natural causes. Farmers with high psychological health pressure can suffer stress. This research aimed to investigate the representation of Stress and the Farmers’ Coping Mechanism in Kalisat-Jember. The type of this research was descriptive and simple random sampling was chosen to collect the data sampling technique. 100 farmers were collected. The respondents were measured by using the farmers’ stress questionnaire and Brief farmers’ coping mechanism questionnaire COPE. The result of stress representation and farmer’s coping mechanism analysis showed that the number of farmer’s stress tends to be the cognitive response. Meanwhile, the result of the coping mechanisms showed that most of the farmer’s coping mechanisms were more focused on emotion rather than problems. The result of this study can be a reference for nurses and primary health care services to diagnose farmers’ health diseases, especially psychological diseases such as stress and coping mechanisms. Nurses can do preventive efforts, interventions, and health education about factors and symptoms of stress and coping mechanisms for the farmers.